(untitled) (Global Journal of Medical Research, 2026)
This article proposes a basic drug formulation that, with additions according to the particular behavior, addresses all psychiatric conditions. The drugs examined are those that address the five major types of brain cells, neurons, astrocytes, oligodendrocytes, endothelial cells and microglia. Approximately 40 drugs need consideration. Five of those drugs have the widest activity but drug-drug interactions eliminate fluoxetine, leaving ketamine, metformin, minocycline, and valproate, as the drugs for formulating a basic treatment for all psychiatric conditions.